Results of infertility treatment using ART methods in patients who underwent myomectomy: risk factors for repeated unsuccessful ART programs - Irena F. Kozachenko; Veronika Y. Smolnikova; Leila V. Adamyan (IP Berlin A.V., 2020)
Aim. To evaluate the results of treatment of patients with uterine fibroids and infertility with ineffective art programs in the anamnesis and to identify possible risk factors for repeated art failures. Materials and methods. 510 patients with uterine fibroids and infertility were examined and surgically treated prior to the ART program. Myomectomy was performed using various approaches: laparoscopic access in 250 patients, laparotomic access in 70 patients, hysteroscopic myomectomy in 100 patients, and combined access (laparoscopic and hysteroscopic) in 90 women. Results. Primary infertility was observed in 38.0%, secondary in 62.0% of patients. The average duration of infertility was 4.41.9 years. ART had in history 54.5% of patients. During the follow-up period up to 2 years, 24.3% of women had recurrent uterine fibroids. After carrying out of surgical treatment and the following ART pregnancy was achieved in 44.3% of patients. Pregnancies ended in childbirth in 58.8% of cases, which exceeded the total share (41.6%) of adverse pregnancy outcomes (ectopic pregnancy, abortions, spontaneous miscarriages at various times) by 1.4 times. Conclusion. Risk factors for repeated ART failures in patients who have undergone myomectomy are: age over 40 years; duration of infertility for more than 5 years and the presence of 3 or more ineffective IVF attempts in the history; the presence of previous surgical interventions such as uterine artery embolization and FUS-ablation; the presence of submucous fibroids, a dominant node located close to the uterine cavity and myoma with signs of blood supply disorders; the combination of uterine fibroids with external genital endometriosis and chronic endometritis.